2010
DOI: 10.1038/cdd.2010.162
|View full text |Cite
|
Sign up to set email alerts
|

p75 neurotrophin receptor mediates apoptosis in transit-amplifying cells and its overexpression restores cell death in psoriatic keratinocytes

Abstract: p75 neurotrophin receptor (p75NTR) belongs to the TNF-receptor superfamily and signals apoptosis in many cell settings. In human epidermis, p75NTR is mostly confined to the transit-amplifying (TA) sub-population of basal keratinocytes. Brainderived neurotrophic factor (BDNF) or neurotrophin-4 (NT-4), which signals through p75NTR, induces keratinocyte apoptosis, whereas b-amyloid, a ligand for p75NTR, triggers caspase-3 activation to a greater extent in p75NTR transfected cells. Moreover, p75NTR co-immunoprecip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 41 publications
3
62
0
Order By: Relevance
“…Although it is widely accepted that p75 has a pro‐apoptotic role in neural cells [Blochl and Blochl, ], few studies documenting the apoptotic aspects of p75 in epithelial cells have been reported. Recently, Truzzi et al [] demonstrated that the activation of p75 facilitates apoptosis in skin keratinocytes, supporting our finding of BDNF‐induced cleaved caspase‐3 expression and TUNEL‐positive apoptotic cells among gingival epithelial cells. Importantly, consistent with the present study, JNK phosphorylation caused by BDNF via p75 was responsible for the skin keratinocyte apoptosis.…”
Section: Discussionsupporting
confidence: 91%
“…Although it is widely accepted that p75 has a pro‐apoptotic role in neural cells [Blochl and Blochl, ], few studies documenting the apoptotic aspects of p75 in epithelial cells have been reported. Recently, Truzzi et al [] demonstrated that the activation of p75 facilitates apoptosis in skin keratinocytes, supporting our finding of BDNF‐induced cleaved caspase‐3 expression and TUNEL‐positive apoptotic cells among gingival epithelial cells. Importantly, consistent with the present study, JNK phosphorylation caused by BDNF via p75 was responsible for the skin keratinocyte apoptosis.…”
Section: Discussionsupporting
confidence: 91%
“…CD271 was firstly isolated from a melanoma cell line and is expressed on neural crest cells from which melanocytes are derived (Kruger et al, 2002). It belongs to the TNF receptor superfamily and mediates apoptosis in different cell settings via its own signaling pathway (Kraemer et al, 2014;Truzzi et al, 2011;Blöchl and Blöch, 2007). The interaction of apoptosis related protein APR-1 with CD271 activate apoptosis in melanoma cells (Selimovic et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…BDNF shows its effect by triggering keratinocyte apoptosis via p75NTR (26). Truzzi et al (26) observed that the apoptosis triggered by the BDNF and p75NTR interaction was significant in keratinocytes in the normal skin but not in psoriatic skin. In our study, the low BDNF infiltration levels in epidermis and dermis in psoriasis patients support these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Autocrine NGF protects the cells from programmed cell death (26). The NGF levels were higher in the epidermis in psoriatic skin than in healthy skin and psoriatic skin without lesions (26).…”
Section: Discussionmentioning
confidence: 99%